Genetic structure of teak beehole borer, Xyleutes ceramicus (Lepidoptera: Cossidae), in northern Thailand - Panyamang, Atikan; Duangpakdee, Orawan; Rattanawannee, Atsalek (Agriculture and Natural Resources, 2018)
The teak beehole borer (Xyleutes ceramicus Walker) is one of the most serious insect pests of teak (Tectona grandis L.f.) in both natural forests and plantations in Thailand, especially in the northern part of the country. Larvae of X. ceramicus infest a living teak tree by burrowing a long tunnel in the trunk, which reduces the quality and value of the marketable timber. To determine the genetic structure of the species, the sequences were examined of two mitochondrial genes (COI and 16S rRNA) and one nuclear gene (EF1-alpha) of 41 individuals collected from 14 teak plantation sites in northern Thailand. The results of the sequencing analysis indicated the presence of 32 mitochondrial and 8 nuclear haplotypes. The phylogenetic analysis results revealed that all haplotypes were highly interconnected and a weak phylogeographic structure was revealed. The low genetic distance (FST) and high per-generation female migration rate (Nm) of most population pairs suggested that long-distance dispersal and the absence of a geographic barrier to gene flow were significant factors that affected the demography of X. ceramicus in northern Thailand.